Healthcare professionals' perceptions of a digital parental support, Childbirth Journey, constructed as a serious game—An intervention study - Bäckström, Caroline; Knez, Rajna; Larsson, Margaretha (Frontiers in Digital Health, 2023)
Background Globally, the digital sources developed and available in antenatal care differ, and infrastructure challenges may impede the further development of such sources. Challenges accompanying digital developments can include the commonly occurring high workload, which affects healthcare professionals’ ability to acquire professional knowledge about how to best support parents in using digital sources. Including healthcare professionals in the development process of digital sources may increase the likelihood that such sources will be adopted and employed by these professionals in their future care work. Therefore, the present research explored healthcare professionals’ perceptions of the digital support intervention Childbirth Journey, which was constructed as a serious game for expectant parents. Methods Data were collected through semi-structured focus-group interviews with 11 midwives at antenatal, labour and postnatal clinics as well as with child healthcare nurses. Prior to the interviews, all participants were provided the intervention, Childbirth Journey, which is a serious game in a mobile application format consisting of two distinct parts: (1) a story-driven game and (2) a Knowledge Portal. The data were analysed using phenomenographic methods. Results The perceptions of Childbirth Journey by healthcare professionals, midwives and child healthcare nurses are presented in four descriptive categories: extended professional support, trustworthy contents, diversity or individuality, and both appealing and in need of development. Conclusions Current study revealed that Childbirth Journey may be utilised as a digital support for parents, allowing healthcare professionals to offer a digital solution as a complementary support to standard, face-to-face meetings with caregivers. However, the research results also revealed that some elements of Childbirth Journey must be improved, thereby representing a main contribution of this study: insights into how to better develop digital tools under the umbrella of health care. Thus, we conclude that in order to create sustainable and safe digital care solutions that function as trustworthy professional supports instead of technical products that risk harming users, the perspectives of both patients and healthcare professionals should be considered in the exploration and development of these solutions.